Repurposing Cholinesterase Inhibitors as Antidepressants? Dose and Stress-Sensitivity May Be Critical to Opening Possibilities - Fitzgerald, Paul J.; Hale, Pho J.; Ghimire, Anjesh; Watson, Brendon O. (Frontiers in Behavioral Neuroscience, 2021)
When stress becomes chronic it can trigger lasting brain and behavioral changes including Major Depressive Disorder (MDD). There is conflicting evidence regarding whether acetylcholinesterase inhibitors (AChEIs) may have antidepressant properties. In a recent publication, we demonstrated a strong dose-dependency of the effect of AChEIs on antidepressant-related behavior in the mouse forced swim test: whereas the AChEI donepezil indeed promotes depression-like behavior at a high dose, it has antidepressant-like properties at lower doses in the same experiment. Our data therefore suggest a Janus-faced dose-response curve for donepezil in depression-related behavior. In this review, we investigate the mood-related properties of AChEIs in greater detail, focusing on both human and rodent studies. In fact, while there have been many studies showing pro-depressant activity by AChEIs and this is a major concept in the field, a variety of other studies in both humans and rodents show antidepressant effects. Our study was one of the first to systematically vary dose to include very low concentrations while measuring behavioral effects, potentially explaining the apparent disparate findings in the field. The possibility of antidepressant roles for AChEIs in rodents may provide hope for new depression treatments. Importantly, MDD is a psychosocial stress-linked disorder, and in rodents, stress is a major experimental manipulation for studying depression mechanisms, so an important future direction will be to determine the extent to which these depression-related effects are stress-sensitive. In sum, gaining a greater understanding of the potentially therapeutic mood-related effects of low dose AChEIs, both in rodent models and in human subjects, should be a prioritized topic in ongoing translational research.